Chemical composition and rumen fermentation profile of mangrove leaves (Avicennia marina) from West Sumatra, Indonesia - Novirman Jamarun; Roni Pazla; Arief ARIEF; Anuraga Jayanegara; Gusri Yanti (Society for Indonesian Biodiversity, 2020)
Abstract. Jamarun N, Pazla R, Arief, Jayanegara A, Yanti G. 2020. Chemical composition and rumen fermentation profile of mangrove leaves (Avicennia marina) from West Sumatra, Indonesia. Biodiversitas 21: 5230-5236. This study aimed to determine the potential of mangrove leaves of Avicennia marina for ruminant animal feed. Laboratory tests were carried out on A. marina with three replicates. Parameters measured were proximate and fiber contents, rumen fluid profile (pH, NH3 and VFA), digestibility of nutrients (DM, Ash, CP, CF, NDF, ADF, cellulose, and hemicellulose), macro and micro mineral contents, and phytochemical compounds. The results showed the nutritional content of A. marina were CP 13.37%; Ash 7.17%; lignin 7.34%; TDN 79%, rumen fluid profile is in reasonable condition, digestibility of food substances is more than 50%, rich in macro and micro minerals and contains phytochemical compounds such as phenols, steroids, triterpenoids, and tannins. Macro and micro minerals content of Ca 0.38%, Na 0.20%, Mg 0.20%, K 0.48%, P 0.51%, S 0.01%, Cl 1.03%, Fe 388 ppm, Zn 164 ppm, Mn 211 ppm, and Cu 128 ppm. This research concludes that A. marina is very potential to be used as a ruminant animal feed.